2013
DOI: 10.2478/pjs-2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of the pancreas in course of acute pancreatitis during treatment with Ulinastatin

Abstract: Application for the treatment of UTI leads to inhibition of the inflammatory process at the stage of pancreatic edema and in cases of severe necrotizing course limits the progression of the disease which gives grounds for its clinical use in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Four-micrometer sections were stained with hematoxylin and eosin (H&E) to observe the morphological changes under the light microscope. The degree of development of pancreatic lesions was evaluated according to point Spormann scale, as previously described [ 20 ]. Histological analysis was conducted in control group, SAP group, and SAP treated with ulinastatin group (30000U/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Four-micrometer sections were stained with hematoxylin and eosin (H&E) to observe the morphological changes under the light microscope. The degree of development of pancreatic lesions was evaluated according to point Spormann scale, as previously described [ 20 ]. Histological analysis was conducted in control group, SAP group, and SAP treated with ulinastatin group (30000U/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, peritoneal lavage and antiprotease therapy may bring an improved therapeutic effect through being applied locally to the peritoneal cavity ( 10 ). The glycoprotein ulinastatin is widely used to treat patients with SAP via the intravenous route ( 11 , 12 ); one of its therapeutic functions is regulation of the inflammatory response. Ulinastatin may provide a greater therapeutic effect for SAP if administered by peritoneal lavage as only a small amount of intravenously administered ulinastatin is able to reach the pancreas and other organs because of microcirculatory dysfunction ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies in humans have not shown a significant improvement in survival with peritoneal antiprotease lavage therapy, it was reported that this treatment could counteract the development of pancreatic necrosis for patients with SAP and reduce the need for surgical intervention (12,15,16). Ulinastatin is a purified glycoprotein from healthy adult male urine, and numerous studies suggest that it has a significant therapeutic effect on SAP (17)(18)(19). In previous years, ulinastatin has been widely used for the treatment of patients with SAP in Asia.…”
Section: Discussionmentioning
confidence: 99%